Working life and human capital investment: Causal evidence from a pension reform - Elisabeth Fürstenau; Niklas Gohl; Peter Haan; Felix Weinhardt (Labour Economics, 2023)
In this paper, we analyze if an increase in the working life leads to more human capital investment via on- the-job training. We obtain RDD-estimates from a sharp date-of-birth cut-off, generated by a pension reform that increased the Early Retirement Age (ERA) by three years for many women in Germany. In our preferred specification, we find that this reform causally increased on-the-job training by 4.4 percentage points - a relative increase of 28.8 percent. We explore heterogeneity and additional outcomes and show that this effect is driven by the behavior of women with high initial levels of education. Our results speak to human capital models as well as policies towards extending or shortening working life.
Keywords: J24; J26; H21; 330; Human capital; retirement policies; RDD